2019
DOI: 10.1186/s12866-019-1642-0
|View full text |Cite
|
Sign up to set email alerts
|

N-acetyltransferase AAC(3)-I confers gentamicin resistance to Phytophthora palmivora and Phytophthora infestans

Abstract: BackgroundOomycetes are pathogens of mammals, fish, insects and plants, and the potato late blight agent Phytophthora infestans and the oil palm and cocoa infecting pathogen Phytophthora palmivora cause economically impacting diseases on a wide range of crop plants. Increasing genomic and transcriptomic resources and recent advances in oomycete biology demand new strategies for genetic modification of oomycetes. Most oomycete transformation procedures rely on geneticin-based selection of transgenic strains.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 63 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…The most common gram-negative member of the AME genes they carry is aac (6′) -Ib ( Ramirez and Tolmasky, 2010 ; Shaul et al, 2011 ; Herzog et al, 2012 ). N-acetyltransferase AAC (3)-I was established as a selectable marker for gentamicin-based oomycete transformation, and it was found that N-acetyltransferase AAC (3)-I was responsible for gentamicin resistance in phytophthora palmivora and phytophthora infestans ( Evangelisti et al, 2019 ).…”
Section: Bacterial Resistance Mechanism To Aminoglycoside Antibioticsmentioning
confidence: 99%
“…The most common gram-negative member of the AME genes they carry is aac (6′) -Ib ( Ramirez and Tolmasky, 2010 ; Shaul et al, 2011 ; Herzog et al, 2012 ). N-acetyltransferase AAC (3)-I was established as a selectable marker for gentamicin-based oomycete transformation, and it was found that N-acetyltransferase AAC (3)-I was responsible for gentamicin resistance in phytophthora palmivora and phytophthora infestans ( Evangelisti et al, 2019 ).…”
Section: Bacterial Resistance Mechanism To Aminoglycoside Antibioticsmentioning
confidence: 99%
“…The seeds were germinated on half-strength Murashige & Skoog medium including B5 vitamins (Duchefa Biochemie, Haarlem, the Netherlands) with 1% bactoagar, pH 5.7, and allowed to grow for 17 days at 25˚C under a 16-hour photoperiod. Roots of 17-day-old seedlings were inoculated with 10 μL zoospore solution from P. palmivora LILI [63], which had been transformed anew with pTOR-tdTomato fluorescent reporter provided by Dr Stephen Whisson (The James Hutton Institute, Dundee, UK) following the protocol described by Evangelisti and colleagues [64]. Zoospores were harvested as previously described [65] and diluted to the concentration of 20,000 zoospores/mL (200 zoospores/seedling).…”
Section: Phytophthora Infection Assaymentioning
confidence: 99%